2020
DOI: 10.1111/srt.12857
|View full text |Cite
|
Sign up to set email alerts
|

Seasonal variations of epidermal biophysical properties in Kunming, China: A self‐controlled cohort study

Abstract: The skin is the largest organ of the human body, covering an area of approximately 2 m 2 in adult. The skin functions as multiple barriers, such as permeability barrier, microbial barrier, and immune barrier, protecting the skin against various insults. Among these barriers, epidermal permeability barrier prevents substances in and out the body through the skin, while melanin serves as epidermal pigment barrier, protecting the skin from excessive ultraviolet (UV) radiation. 1 Recent studies demonstrated that e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
19
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(21 citation statements)
references
References 24 publications
(29 reference statements)
2
19
0
Order By: Relevance
“…Winter is usually associated with lower sebum content in comparison with summer 19,21,23‐25,28,30,87 as we also observed in our study on the forehead. Several studies observed different results probably due to the overall lower sebum levels of the subjects (usually lower than 60 µg.cm ‐2 ) where the changes were not so prominent 16,18‐20,23,30,31 . Similar results were observed in our study on the cheek where the trend of higher sebum content in summer and spring was visible as well but was not statistically significant.…”
Section: Discussionsupporting
confidence: 87%
See 3 more Smart Citations
“…Winter is usually associated with lower sebum content in comparison with summer 19,21,23‐25,28,30,87 as we also observed in our study on the forehead. Several studies observed different results probably due to the overall lower sebum levels of the subjects (usually lower than 60 µg.cm ‐2 ) where the changes were not so prominent 16,18‐20,23,30,31 . Similar results were observed in our study on the cheek where the trend of higher sebum content in summer and spring was visible as well but was not statistically significant.…”
Section: Discussionsupporting
confidence: 87%
“…1). The vast majority of the studies found decreased SC hydration in winter as we also confirmed 11‐32 . Only a few studies observed no or opposite trends in some specific cases 13,16‐18,33 …”
Section: Discussionsupporting
confidence: 82%
See 2 more Smart Citations
“…3 Many studies have reported that these skin biophysical parameters changed according to age, gender, anatomical regions and seasons in different ethnic populations. [4][5][6][7][8][9][10][11] Man et al demonstrated that the skin surface pH, sebum content and SC hydration varied with age, gender and body site in a large Chinese population. 12 Mayes et al reported that the facial skin L*a*b* skin colors, hydration and TEWL had associations with chronological age in Chinese females.…”
Section: Introductionmentioning
confidence: 99%